Patterns of livelihood diversification in farming systems of the Eastern Gangetic Plains - Jackson, Tamara M.; Nandi, Ravi; Jannat, Arifa; Ghosh, Arunava; Hajra, Dilip Kumar; Mitra, Biplab; Rashid, Md Mamunur; Bista, Sagar; Chaudhary, Anjana; Timsina, Pragya; Karki, Emma; Chakma, Kali Rattan; et al. (Elsevier, 2025)
CONTEXT The Eastern Gangetic Plains (EGP) is a region characterized by smallholder-dominated farming systems, facing rapid socio-economic and environmental changes. Livelihood diversification away from traditional agriculture is increasingly seen as a strategy to enhance resilience, income stability, and food security among these smallholders. However, comprehensive understanding of diversification patterns and their drivers within the EGP remains limited. OBJECTIVE This study aims to elucidate the patterns of livelihood diversification in farming systems across the EGP, and identify the key factors driving diversification. METHODS Utilizing data from the Rupantar project involving a baseline survey of 1400 households across India, Nepal, and Bangladesh, and a subsequent analysis employing the Simpson's Index of Diversity (SID) to quantify diversification levels. Multivariate regression models were used to explore the determinants of diversification, while disaggregating the analysis by country and diversification components (crop plot, crop non-plot, and non-crop non-plot). RESULTS AND CONCLUSION The study revealed moderate levels of diversification across the EGP, with significant geographical and contextual variability. Key drivers of diversification included access to resources, gender, education, market access, and institutional support, with notable differences across countries and diversification types. Specifically, non-ownership of irrigation pumps, female household headship, and engagement in off-farm and non-farm activities emerged as significant predictors of higher diversification levels. SIGNIFICANCE This study contributes to a nuanced understanding of livelihood diversification in the EGP, highlighting the complexity of diversification patterns and the multifaceted nature of its determinants and impacts. By identifying specific drivers of diversification, the findings provide valuable insights for policymakers, development practitioners, and researchers aiming to support rural livelihoods in the region. Emphasizing the role of gender, resource access, and institutional support, the study underscores the importance of tailored interventions to enhance the resilience and sustainability of smallholder farming systems in the face of changing environmental and socio-economic conditions.